A review of paratuberculosis in dairy herds — Part 1: Epidemiology. (April 2019) - McAloon, Conor G.; Roche, Steven; Ritter, Caroline; Barkema, Herman W.; Whyte, Paul; More, Simon J.; O'Grady, Luke; Green, Martin J.; Doherty, Michael L.
Highlights: The controversial link between Mycopbacterium avium subspecies paratuberculosis (MAP) and Crohn's disease is a potential threat to the industry. Pasteurisation does not completely eliminate MAP, therefore control must be implemented at farm level to minimise exposure. There is some evidence that participation in a control programme reduces the prevalence of the disease. However, there is little evidence in support of the impact of specific control measures on the incidence of MAP infection. Modelling studies suggest that vaccination may be an attractive option, but use is limited where cattle are tested for TB. Abstract: Bovine paratuberculosis is a chronic infectious disease of cattle caused by Mycobacterium avium subspecies paratuberculosis (MAP). This is the first in a two-part review of the epidemiology and control of paratuberculosis in dairy herds. Paratuberculosis was originally described in 1895 and is now considered endemic among farmed cattle worldwide. MAP has been isolated from a wide range of non-ruminant wildlife as well as humans and non-human primates. In dairy herds, MAP is assumed to be introduced predominantly through the purchase of infected stock with additional factors modulating the risk of persistence or fade-out once an infected animal is introduced. Faecal shedding may vary widely between individuals and recent modelling work has shed some light on the role of super-shedding animals in the transmission of MAP within herds. Recent experimental work has revisited many of the assumptions around age susceptibility, faecal shedding in calves and calf-to-calf transmission. Further efforts to elucidate the relative contributions of different transmission routes to the dissemination of infection in endemic herds will aid in the prioritisation of efforts for control on farm.